A critical review of analytical methods for ergot alkaloids in cereals and feed and in particular suitability of method performance for regulatory monitoring and epimer-specific quantification. Issue 6 (3rd June 2021) - Chung, Stephen W.C.
ABSTRACT: Cereals and feed contaminated with ergot alkaloids (EAs) have been of concern for several decades. Nowadays, analysis of EAs is focused on ergometrine, ergotamine, ergosine, ergocristine, ergocryptine (a mixture of α- and β-isomers) and ergocornine and their related –inine epimers as listed in the European Commission Recommendation 2012/154/EU. Liquid chromatography with fluorescence detection has been used for quantification of EAs for decades whilst LC–MS has become the work-horse for quantification of EAs in the last decade. However, in LC–MS analysis matrix effects of different magnitudes exist for each EA epimer, especially ergometrine/ergometrinine, even after different clean-up procedures. This leads to an underestimation or overestimation of EAs levels. Moreover, isotopic labelled standards for EAs are still not available in the market. This review aims to provide background information on different analytical methods, discuss their advantages and disadvantages and possible advancement. Moreover, the method performance requirements to support forthcoming regulations are also discussed.